Lili [videorecording (DVD)] - Walters, Charles, 1911-1982; Caron, Leslie; Ferrer, Mel; Aumont, Jean Pierre; Gallico, Paul, 1897-1976 (Archive collection., 2012)
After an orphaned young woman joins a carnival, she falls under the romantic spell of a magician while the puppeteer secretly falls in love with her and can only express his feelings through his puppets.